Functional Status of Neonatal and Pediatric Patients after Extracorporeal Membrane Oxygenation - Cashen, Katherine (Pediatr Crit Care Med, 2017)
OBJECTIVE: To describe functional status at hospital discharge for neonatal and pediatric patients treated with extracorporeal membrane oxygenation (ECMO), and identify factors associated with functional status and mortality. DESIGN: Secondary analysis of observational data collected by the Collaborative Pediatric Critical Care Research Network (CPCCRN) between December 2012 and September 2014. SETTING: Eight hospitals affiliated with the CPCCRN. PATIENTS: Patients were <19 years of age and treated with ECMO. INTERVENTIONS: Functional status was evaluated among survivors using the Functional Status Scale (FSS). Total FSS scores range from 6–30 and are categorized as 6–7 (good), 8–9 (mildly abnormal), 10–15 (moderately abnormal), 16–21 (severely abnormal) and >21 (very severely abnormal). MEASUREMENTS AND MAIN RESULTS: Of 514 patients, 267 (52%) were neonates (≤30 days old). Indication for ECMO was respiratory for 237 (46%), cardiac for 207 (40%) and extracorporeal cardiopulmonary resuscitation (eCPR) for 70 (14%). Among 282 survivors, 89 (32%) had good, 112 (40%) mildly abnormal, 67 (24%) moderately abnormal, and 14 (5%) severely or very severely abnormal function at hospital discharge. Among neonates, development of renal failure and longer hospitalization were independently associated with worse FSS. Chronic conditions, prematurity, venoarterial ECMO, increased red cell transfusion in the first 24 hours of ECMO, and longer ECMO duration were independently associated with mortality. Among pediatric patients, chronic neurologic conditions, tracheostomy or home ventilator, eCPR, hepatic dysfunction and longer intensive care unit stay were independently associated with worse FSS. Chronic cardiac conditions, hepatic dysfunction, and neurologic or thrombotic complications were independently associated with mortality. Achieving blood lactate concentration ≤2 mmol/L during ECMO was independently associated with survival in both neonatal and pediatric patients. CONCLUSIONS: In this study, about half of ECMO patients survived with good, mildly abnormal or moderately abnormal function at hospital discharge. Patient and ECMO related factors are associated with functional status and mortality.